Experimental and analytical assessment of a packed bed for thermal energy storage - Khor, Jun Onn (Nanyang Technological University, 2021)
Liquefied natural gas (LNG) is a preferred distribution method for natural gas, particularly for long distance transport. LNG is regasified before distributed to the final consumers, releasing vast amount of cold energy. Majority studies on recovery of LNG cold energy involve conversion of cold energy into electricity. Usage of other energy carriers such as working fluids and thermal energy storage (TES) are seldom considered. When cold demands exist, cold-to-cold transfer from LNG terminal to demands using electricity as energy carrier can be unfeasible due to extra conversion process required. A study is carried out to compare the performances of different energy carriers, including electricity, working fluids, solid-liquid type phase change materials (PCMs) storage and liquid air energy storage (LAES), to transport LNG cold energy to different cold demands. Four cold demands (air separation, dry ice production, deep-freezing warehouse and district cooling system) are considered, with their setups altered to adapt with different energy carriers. Layouts and performances of different cold demands subjected to different cold carriers are investigated in detail. On overall, using working fluids and PCM TES energy carriers result in 38.0% and 37.0% reduction in carbon emissions, which can be attributed to the replacement of conventional cooling systems in most cold demands supported by these energy carriers. Using LAES yields only 6.0% reduction in carbon emissions, due to the energy-intensive liquid air production process. Considering the costs and feasibility between working fluids and TES for cold distribution, TES is chosen as the next subject of study due to its lower capital and operational costs. TES systems have been widely investigated for heat applications, but less for cold storage, while majority of them focus on low-grade cold storage such as space cooling. Study of TES systems for storage of LNG cold is the first-of-its-kind during the point the study was carried out. A numerical study is carried out using Galden HT-55 as liquid-state heat transfer fluid (HTF) and has operating temperature as low as -80°C. Cascaded PCM in packed bed configuration (different PCM arranged in series), known with higher operational efficiencies, is chosen with three PCMs with different melting temperatures (-49°C, -19.5°C and 6.5°C). The study serves two objectives: (1) to find out the performance of PCM storage for low-temperature cold storage, especially in the real life where PCM’s thermophysical properties deteriorates with decrease of phase change temperature, and (2) to minimize the amount of PCMs for optimum performances. Such optimization study is important as a lot of the time, TES systems act as auxiliary systems to other thermal systems, and their parameters are seldom optimized. The performances of TES system are evaluated based on the operation time and cyclic efficiencies on different TES capacity for each PCM. Cyclic efficiency is found to be the highest when ratio of TES capacity for high-medium-low grade PCMs is 10:7:5. Besides, with all the simulated cases, a generalized map is presented. The map allows a user to predict the performance of a cascaded PCM system with pre-determined storage capacity for each PCM. Besides, if the user has desired performance for the system, the map can be used to determine the suitable allocation of TES capacity for each PCM. Liquid HTF based TES system has higher operating temperature and is unable to fully utilize all exergy of LNG cold, despite the high energy density of the HTF. Gaseous type HTF is thus investigated for charging an in-house-developed PCM. Due to lack of reported experiment for cold storage at temperature as low as -160°C, a packed bed TES experimental setup using in-house-developed PCM is thus built to achieve two purposes: (1) to obtain experimental results for more accurate validation of 3-D simulation models due to clearer understanding on the operating conditions and (2) to investigate a high-grade cold TES system using gaseous type HTF. This TES for such high-grade cold storage (PCM with melting temperature of -118°C) is the first-of-its-kind. From the experiments, the large void space in between the encapsulated PCMs which contributed to zero TES capacity and low efficiency of the system is identified as a key improvement area. Granular quartzite pebbles are inserted into the void space to reduce the void fraction. Experiments are then carried out to validate a new numerical model which considers two TES materials in a same numerical grid. Consideration of homogenous mixture of granular materials with PCM is never considered to improve performance of a packed bed PCM TES system. Thus, numerical studies are carried out to identify the influence of different granular materials under systems with different PCMs, encapsulation size and HTF flow rate. Insertion of granular materials improves the TES efficiency by up to 25%, particularly when the PCMs have ultra-low phase change temperature, due to materials’ limitations with thermo-physical properties. Granular materials allow for increase in encapsulation size by up to 60% and decreases encapsulation cost by up to 75% without deteriorating performance of the system. Alumina particles are found to be the best granular material due to the extra storage capacity it provides due to its high density. Using micro-encapsulated PCM (n-decane) brings the highest improvement in cyclic efficiency, however, it is found that if micro-encapsulated PCM with lower phase change temperature is developed, the system performance can be further improved. Thus far, 1-dimensional model has been used for numerical studies. However, some parameters of the TES system cannot be studied with 1-dimensional model, such as development of radial temperature profile due to energy loss via the tank wall, as well as additional of inlet from the side where radial flow component needs to be studied. A 3-dimensional COMSOL simulation model is built and validated with the experimental results to study the development of temperature profile in both axial and radial directions of a TES tank, as well as change in performance of system under influence of auxiliary input with different HTF flow direction. Due to the thermal energy via tank wall, it is found that the temperature gradient along HTF axial-flow direction increases, which elongates the charge time of a TES system as PCMs near the tank wall is subjected to reduced thermal power. Side injection inlets are thus proposed to supply HTF with high-grade cold energy directly, to increase the thermal power in the region near the tank wall. However, usage of side inlet alone is unable to solve the problem directly, as mixing occurs between diverted flow from the side inlet and the flow from the main inlet, resulting in great exergy losses, especially if the resultant mixture has temperature higher than the PCM phase change temperature. Thus, operational parameters are also considered where at the beginning of the charging stage, only main inlet is used. After a certain amount of time, part of the flow entering the main inlet is redirected to the side inlet, while maintaining the total flow rate into the system. Such configuration is found to able to decrease the charge time by up to 13.4%. The abovementioned study identified three aspects on how a TES system designed for cryogenic cold storage can be designed and improved. When all the aspects are considered during design stage, there is no doubt that an optimized TES system, not only for storage of LNG cold, but also for a generic storage of thermal energy can be designed.